IMPACTS OF SUGAR IMPORT POLICY ON SUGAR PRODUCTION IN INDONESIA - Agustinus Suryantoro; Albertus Magnus Susilo; Supriyono Supriyono (KINERJA, 2013)
Production of sugar unful lled consumption of Indonesia society. The lack of consumption and productionhave ful lled by import. Assumption national consumption 2,7 million ton, Indonesia will import sugar in 2013predicted about 300.000 ton (Tempo.co, August, 21, 2012).The aims in general of this research are to understand the impact of sugar import policy on sugar production.Especially (1) to understand the factors that in uence sugar import price, (2) to understand impact of sugarimport price on sugar domestic price and (3) to understand the impact of sugar domestic price on sugarproduction.Model analysis of this research is Simultaneous Error Correction Model. This model can estimate the structuralparameter exactly (unbiased parameter) (Gujarati, 2010). Policy made on this research can be responsibly.The results of this research are shown that price of sugar import in uenced by world sugar price and thequantity of sugar imported and tariff is not. Price of domestic sugar in uenced imported sugar price. Anddomestic sugar price has in uence the sugar production.Import policy in sugar to ful ll lack of consumption and production will make decreased sugar domestic price.The decrease of sugar domestic price will impact on decrease of sugar production. That policy have dilemmaon consumption and production.Keywords: sugar imported, price of sugar imported, sugar domestic price, sugar production and policy dilemma.